2016
DOI: 10.1016/j.biortech.2016.06.074
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic co-digestion of acetate-rich with lignin-rich wastewater and the effect of hydrotalcite addition

Abstract: The methane potential and biodegradability of different ratios of acetate and lignin-rich effluents from a neutral sulfite semi-chemical (NSSC) pulp mill were investigated. Results showed ultimate methane yields up to 333±5mLCH4/gCOD when only acetate-rich substrate was added and subsequently lower methane potentials of 192±4mLCH4/gCOD when the lignin fraction was increased. The presence of lignin showed a linear decay in methane production, resulting in a 41% decrease in methane when the lignin-rich feed had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…However, the yield remained lower than that obtained with nickel based LDH. Recently, three LDH (FeMg−Al, ZnMg−Al and FeZnMg−Al) have been tested in the anaerobic digestion of synthetic sulfate‐containing wastewater in order to evaluate their effect on the methane production ,. An enhancement of CH 4 production was observed in the presence of the FeZnMg−Al LDH.…”
Section: Applications Of Bacteria@ldh Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the yield remained lower than that obtained with nickel based LDH. Recently, three LDH (FeMg−Al, ZnMg−Al and FeZnMg−Al) have been tested in the anaerobic digestion of synthetic sulfate‐containing wastewater in order to evaluate their effect on the methane production ,. An enhancement of CH 4 production was observed in the presence of the FeZnMg−Al LDH.…”
Section: Applications Of Bacteria@ldh Assembliesmentioning
confidence: 99%
“…Indeed, Rodriguez‐Chiang et al . report that microbial growth was higher in all samples containing LDH compared to the control samples with no LDH . Moreover, it was also suggested that during the fermentation processes, metals (Ni 2+ , Mg 2+ or Fe 2 +, Zn 2+ ) were released from the LDH layers under acidic conditions and those cations may boost the enzymatic activities.…”
Section: Applications Of Bacteria@ldh Assembliesmentioning
confidence: 99%
“…a, b, c and n are the molar content of the substrate for hydrogen, oxygen, nitrogen and carbon, respectively. Where TBMP L is the theoretical biochemical methane potential for liquid substrate (NLCH 4 KgVS -1 ), 0.35 NL is the theoretical CH 4 yield of 1 g COD at STP [19], VS is the volatile solids of the substrate (kg L -1 ) and OM is the organic matter concentration, in terms of COD (gO 2 L -1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from biomass samples collected from both reactors at the beginning of the experiments (day 0), then on days 5,8,12,15,22,33,36,50, 57 and 68, and at the end of the experiments (day 75). DNA was extracted from the samples by the following steps: 0.1 g of biomass was washed in sodium phosphate buffer (0.1 M; pH 8.0) and pelleted by centrifugation.…”
Section: Dna Extractionmentioning
confidence: 99%
“…It is well documented that the presence of a lignin fraction, especially a low molecular fraction of this substance, induces methanogenic toxicity and inhibits bacterial growth [21]. Rodriguez-Chiang et al [22] evaluated the methane potential and biodegradability of acetate and lignin-rich pulp mill effluent at different ratios using mesophilic anaerobic sludge as inoculum. They found a negative linear correlation between lignin content and methane yield.…”
Section: Biogas/methane Productionmentioning
confidence: 99%